Short peptides from leucyl-tRNA synthetase rescue disease-causing mitochondrial tRNA point mutations. (31st December 2015) - Perli, Elena; Fiorillo, Annarita; Giordano, Carla; Pisano, Annalinda; Montanari, Arianna; Grazioli, Paola; Campese, Antonio F.; Di Micco, Patrizio; Tuppen, Helen A.; Genovese, Ilaria; Poser, Elena; Preziuso, Carmela; et al.
Abstract : Mutations in mitochondrial (mt) genes coding for mt-tRNAs are responsible for a range of syndromes, for which no effective treatment is available. We recently showed that the carboxy-terminal domain (Cterm) of human mt-leucyl tRNA synthetase rescues the pathologic phenotype associated either with the m.3243A>G mutation in mt-tRNA Leu(UUR) or with mutations in the mt-tRNA Ile, both of which are aminoacylated by Class I mt-aminoacyl-tRNA synthetases (mt-aaRSs). Here we show, by using the human transmitochondrial cybrid model, that the Cterm is also able to improve the phenotype caused by the m.8344A>G mutation in mt-tRNA Lys, aminoacylated by a Class II aaRS. Importantly, we demonstrate that the same rescuing ability is retained by two Cterm-derived short peptides, β30_31 and β32_33, which are effective towards both the m.8344A>G and the m.3243A>G mutations. Furthermore, we provide in vitro evidence that these peptides bind with high affinity wild-type and mutant human mt-tRNA Leu(UUR) and mt-tRNA Lys, and stabilize mutant mt-tRNA Leu(UUR) . In conclusion, we demonstrate that small Cterm-derived peptides can be effective tools to rescue cellular defects caused by mutations in a wide range of mt-tRNAs.